2008
DOI: 10.1042/bj20080474
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on clathrin-mediated endocytosis

Abstract: Investigations into the mechanisms which regulate entry of integral membrane proteins, and associated ligands, into the cell through vesicular carriers (endocytosis) have greatly benefited from the application of live-cell imaging. Several excellent recent reviews have detailed specific aspects of endocytosis, such as entry of particular cargo, or the different routes of internalization. The aim of the present review is to highlight how advances in live-cell fluorescence microscopy have affected the study of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
131
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 103 publications
(212 reference statements)
1
131
1
2
Order By: Relevance
“…Unlike Notch and JAK-STAT signaling, which are only activated by later blocks in the endolysosomal pathway (e.g., ept and vps25), we find that Yki activity is elevated by manipulating genes at each step in the endolysosomal pathway including AP-2σ, which encodes a component of the AP-2 adaptor complex that recruits cargoes into clathrin-coated pits for subsequent internalization (reviewed in ref. 25). Moreover, we show that Yki …”
Section: Resultsmentioning
confidence: 99%
“…Unlike Notch and JAK-STAT signaling, which are only activated by later blocks in the endolysosomal pathway (e.g., ept and vps25), we find that Yki activity is elevated by manipulating genes at each step in the endolysosomal pathway including AP-2σ, which encodes a component of the AP-2 adaptor complex that recruits cargoes into clathrin-coated pits for subsequent internalization (reviewed in ref. 25). Moreover, we show that Yki …”
Section: Resultsmentioning
confidence: 99%
“…Matters were complicated further when later data suggested that a single CCP could give rise to multiple vesicles (Rappoport, 2008). Single particle analysis of TIRF data showed that some CCV were initiated de novo -that is, the assembly of a single CCP resulted in complete disappearance of clathrin-associated signal into an internalized vesicle.…”
Section: Understanding Clathrin Mediated Endocytosis Via Tirf Microscopymentioning
confidence: 99%
“…However, other CCPs were seen to separate into sub-structures, only a portion of which were seen to internalize, while other CCPs were seen to merge into larger structures (often termed clathrin coated plaques). As an example, Figure 1 shows TIRF images and analysis representing a single event of the latter type, taken from (Rappoport, 2008). Close inspection of the indicated point spread function from a single sub-diffraction sized CCP shows a broadening and eventual separation into two distinct features.…”
Section: Understanding Clathrin Mediated Endocytosis Via Tirf Microscopymentioning
confidence: 99%
“…Reprinted with kind permission from Champion and Mitragotri (2006) 200 nm), which are pinched off from the plasma membrane by a small GTPase, dynamin (Pucadyil and Schmid 2009). Clathrin-coated vesicles lose their clathrin coat upon internalization and fuse with early endosomes, where they are sorted to late endosomes/lysosomes (pH 5.0-6.0), to the trans-Golgi network, or to recycling endosomes to be transported back to plasma membrane (Rappoport 2008). Contrary to phagocytosis, it is difficult to describe a thorough and consistent profile of nanoparticles uptake for CME.…”
Section: Clathrin-mediated Endocytosismentioning
confidence: 99%